Durability of Steel Fibres Reinforcement Concrete Beams in Chloride Environment Combined with Inhibitor - AbdelMonem Masmoudi; Jamel Bouaziz (Advances in Materials Science and Engineering)
This paper presented the effect of the combination of an inhibitor and steel fibre reinforced concrete (SFRC) for concrete structures in chloride environments. Twelve beams were cast and tested to study their flexural behavior. The morphology of steel surfaces using the inhibitor after observing the scanning electron microscope showed a low layer of corrosion products. The steel surface immersed in the inhibitor free solution was seen to have been subject to chloride ions attacks as shown in this study. The interest to the field of the present study is the relatively higher durability of the performance when using the inhibitor. Crack width and crack spacing for beams under the same load showed that the use of SFRC with the inhibitor for concrete structures in chloride environments must have transferred tension across cracks that led to reducing crack spacing without any chloride ions attack.